Genetics of autoimmune diabetes mellitus - Cerná, Marie (Wiener medizinische Wochenschrift (1946), 2008)
Autoimmune diabetes mellitus, called type 1 diabetes mellitus (T1DM), is caused by autoimmune destruction of islet beta cells in the pancreas. T1DM susceptibility loci mapped by different genome screening are IDDM1-IDDM18. It has been estimated that HLA (IDDM1) provides up to 40-50 % of the familial clustering of T1DM (LOD score of 65.8). Many studies have verified that DQB1*0302 is a strong susceptibility gene and that the heterozygous combination of DQA1*0301-DQB1*0302 on the HLA-DR4 haplotype and DQA1*0501-DQB1*0201 on the HLA-DR3 haplotype results in a synergistically increased risk of T1DM. The presence of predisposing genes in autoimmune diabetes decreases with age, probably due to increasing influence of environmental factors. Autoimmune diabetes with manifestation in adults may have partly different immunogenetic etiopathogenesis than autoimmune diabetes with manifestation in childhood. Compared to fast progressing adult-onset T1DM, slowly progressing adult-onset type 1 diabetes (LADA) might involve genes leading to a slow progressive beta-cells destruction.
Keywords: Genetic Predisposition to Disease; Disease Progression; HLA-DR3 Antigen; HLA-DQ beta řetězec; HLA-DQ Antigens; HLA-DR Antigens; progrese nemoci; diabetes mellitus 1. typu; HLA-DR3 antigen; Haplotypes; Adult; HLA-DR4 Antigen; polymorfismus genetický; dítě; Child; věkové faktory; HLA-DR antigeny; HLA-DQ alfa řetězec; Diabetes Mellitus, Type 1; HLA-DQ beta-Chains; Polymorphism, Genetic; autoimunita; Autoimmunity; Humans; autoprotilátky; HLA-DQ antigeny; haplotypy; rizikové faktory; Age Factors; dospělí; genetická predispozice k nemoci; Risk Factors; HLA-DR4 antigen; HLA-DQ alpha-Chains; Autoantibodies; lidé